(untitled) (Sudurpaschim Spectrum, 2024)
The purpose of this study is to explore ethno mathematical knowledge of Byansi Sauka ethnic group. This study is based on interpretative paradigm followed by qualitative research method and ethnographic design. A sample of two persons from Byansi Sauka Community has been taken by purposive sampling method. The result of the study showed that Byansi Sauka developed mathematical counting numbers and expressed them by different words. They used basic twenty words to count objects. The words are Tigai, Nishya, Sum, Pi, Nai, Tugu, Nishe, Jedai, Gui, Chee, Chethi, Cheni, Chesum, Chepi, Chebang, Chedhu, Chyonee, Chebjai, Chirgu, and Nassa, standing respectively for 1,2,3,4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20 in the Hindu Arabic numeral system. All other numbers are formed by these twenty words. They developed a rule of addition, a word placed after another of small value adds its value; e.g., Nassa tigai = 20+1 = 21, Nasha nishya = 20+2 = 22, Nasha sum = 20+3 = 23, Nasha pi = 20 +4, Nasha nai = 20+5=25 and so on. Woolen garments like Chedar (Pankhi), Pye (Chutka), and Sab (Carpet). Lanbyaare associated with geometrical concept of parallel sides, vertices, right angles, rectangle, and square. With the help of sub, we can teach the concept of sides, vertex, right angle, and rectangle, square. From cultural ornaments like Bira, Baha, and Baldang, we can sketch the knowledge of circle. Cultural artifacts Jhamko and Dumbo are cylindrical in shape. We can give the concept of cylinder by using Jhamko and Dumbo as instructional material. To teach the rectangular prism we can sketch the knowledge from cultural artifact Phir, Bhakar, Jung Baksa and Almari.The cultural artifact Ghurra is associated with the concept of Cone. We can use the Ghurra as instructional material for teaching the concept of cone. The musical instrument Damaha is in bowl shaped. When teaching the concept of half sphere, circle radius, diameter and circumference we can use Damaha as instructional material. The musical instrument Dhol is cylindrical double-headed drum and associated with geometrical concept of cylinder, circle, radius, dimeter and circumference.